The Influence of Temperature and Precipitation on Picea Mariana at Treeline - Nocon, Barbara (My University, 1988)
Statistical analyses between the relationship of tree-ring widths with variations in climate were used to examine the limiting climatic factors upon the growth rate of Picea mariana along the treeline and in hopes of reconstructing past climate. Tree-ring widths were used as a proxy measure of growth rates to establish the relationship of annual variances in temperature and precipitation on the growth rate of trees. Twelve tree cores were sampled from separate trees along the treeline northeast of Yellowknife, Northwest Territories. The trees, (with cores spanning 40 -160 years per tree), were compared to monthly and seasonal variations of both temperature and precipitations. A stepwise regression model was used to examine the climate-growth response. No climatic variables were found to illicit a general response pattern. The growth rate of trees along the treeline, northeast of Yellowknife do not appear to be dependent upon variations in the regional climate. Therefore, no climatic reconstructions were possible.
Keywords: influence, temperature, precipitation, Picea Mariana, Treeline, climate